If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x-3)=4(x+6)
We move all terms to the left:
7(x-3)-(4(x+6))=0
We multiply parentheses
7x-(4(x+6))-21=0
We calculate terms in parentheses: -(4(x+6)), so:We get rid of parentheses
4(x+6)
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
7x-4x-24-21=0
We add all the numbers together, and all the variables
3x-45=0
We move all terms containing x to the left, all other terms to the right
3x=45
x=45/3
x=15
| 3x^2-2x-23=-3 | | x+59+89=x+115 | | 28+19u=8+15u | | f(4)=3.14 | | 2x=-44-3(2x+-4) | | u+41/9=8 | | 8x-4+5=2(2x+1)+3 | | 2x-2=5(x=1)=50 | | (5/3)x+(1/3)x=(10/3)+(7/3)x | | (c+3.6)4-2c=9.6 | | 9x+12x-21=27 | | y²=6y* | | y²=6y | | 8-2x=18-4x | | 5(x+8)=x+20 | | (x−1/2)/3=7 | | 8=14-3q | | 2(x-2)=x-5 | | 3/d-10=-2 | | -3^(2)-16=-3x | | -0.3.75c-11=13 | | -3^(2)-16=-x | | -15=3(-6x+5)+3 | | 5^x-2^x=10 | | 6x+3x+1x=180 | | 0.85x+5=15 | | 18x+5=100 | | 2/3x^2-15=0 | | 2+3∣10+x∣=23 | | w+19=22 | | 4d-2=14 | | 56-9x=24-x |